Principles of optics for engineers : diffraction and modal analysis - Chang, William S. C. 1931-2015 (Cambridge University Press, 2015)
Uniting classical and modern photonics approaches by presenting optical analyses as solutions of Maxwell's equations, this book enables students and practising engineers to fully understand the similarities and differences between the different methods. Topics include: plane wave analysis; diffraction analysis of many applications, including a rigorous analysis of TEM waves using Maxwell's equations with boundaries; laser cavity modes and Gaussian beams; modal analysis; approximation methods (including the perturbation technique, coupled mode analysis, and super mode analysis). With theory linked to practical examples throughout, it provides a clear understanding of the interplay between plane wave, diffraction and modal analysis, and how the different techniques can be applied to various areas including imaging, signal processing, and optoelectronic devices. --